2017
DOI: 10.1128/jvi.01596-16
|View full text |Cite
|
Sign up to set email alerts
|

Superiority in Rhesus Macaques of Targeting HIV-1 Env gp140 to CD40 versus LOX-1 in Combination with Replication-Competent NYVAC-KC for Induction of Env-Specific Antibody and T Cell Responses

Abstract: We compared the HIV-1-specific immune responses generated by targeting HIV-1 envelope protein (Env gp140) to either CD40 or LOX-1, two endocytic receptors on dendritic cells (DCs), in rhesus macaques primed with a poxvirus vector (NYVAC-KC) expressing Env gp140. The DC-targeting vaccines, humanized recombinant monoclonal antibodies fused to Env gp140, were administered as a boost with poly-ICLC adjuvant either alone or coadministered with the NYVAC-KC vector. All the DC-targeting vaccine administrations with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…We used the Rhesus macaque model to compare the efficacy for inducing or boosting cellular immunity against HIV-1 by targeting five T cell epitope-rich regions from HIV-1 Gag, Pol, and Nef to the DC receptors DCIR and CD40. Preclinical studies in vitro and in vivo using model antigens provided a framework for selecting humanized anti-DCIR and anti-CD40 DC targeting antibodies as vehicles for delivery of the HIV5pep sequences to a broad array of antigen-presenting cells [1820, 2829, 33], as well as the benefit of poly-IC co-administration as adjuvant for improved T cell immunity [14, 19, 20, 32, 34]. In particular, studies in mice with a humanized immune system showed that poly-IC was superior to other adjuvants for inducing CD8 + cytotoxic T cells response to the CD40-targeting HIV5pep vaccine [35], while a study in Rhesus macaques demonstrated that CD4 + and CD8 + T cell responses to a high dose peptide vaccination were significantly enhanced when an agonistic αCD40 antibody was co-administered with poly-IC [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Rhesus macaque model to compare the efficacy for inducing or boosting cellular immunity against HIV-1 by targeting five T cell epitope-rich regions from HIV-1 Gag, Pol, and Nef to the DC receptors DCIR and CD40. Preclinical studies in vitro and in vivo using model antigens provided a framework for selecting humanized anti-DCIR and anti-CD40 DC targeting antibodies as vehicles for delivery of the HIV5pep sequences to a broad array of antigen-presenting cells [1820, 2829, 33], as well as the benefit of poly-IC co-administration as adjuvant for improved T cell immunity [14, 19, 20, 32, 34]. In particular, studies in mice with a humanized immune system showed that poly-IC was superior to other adjuvants for inducing CD8 + cytotoxic T cells response to the CD40-targeting HIV5pep vaccine [35], while a study in Rhesus macaques demonstrated that CD4 + and CD8 + T cell responses to a high dose peptide vaccination were significantly enhanced when an agonistic αCD40 antibody was co-administered with poly-IC [36].…”
Section: Discussionmentioning
confidence: 99%
“…In non-human primates (NHPs), targeting HIV-1 Gag p24 to various DC receptors including DEC-205 [16], Langerin [17], and DCIR [18] has demonstrated increased antigenicity, as well as the benefits of co-administration with poly-IC adjuvant and the utility for priming immune responses. In other studies, targeting HIV-1 Env gp140 to LOX-1 [19] and CD40 [20] evoked potentially protective humoral and cellular immunity in both priming and viral vector boost settings. To broaden the antigenic repertoire beyond HIV-1 Gag p24 and the highly variable Env gp140, we previously tested in NHPs and humans a set of five lipidated T cell epitope-rich peptides from HIV-1 Gag, Pol, and Nef (HIV5pep) that induced HIV-1-specific CD4 + and CD8 + T cell responses [2125].…”
Section: Introductionmentioning
confidence: 99%
“…Env-specific IgG and IgA responses in serum and in mucosal samples were measured as previously described ( 29 , 52 , 62 ). For quantification of IgA responses, IgG was depleted from sera by use of HP MultiTrap protein G filter plates (GE Healthcare Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, efforts have been made to improve the stability, conformation, and immunogenicity of the Env protein used in preventive vaccines, as well as their delivery to the immune system [13,14]. Our group and others have focused on a strategy to target vaccine antigens to receptors (DEC-205, CD40, DCIR, LOX-1, Langerin) on dendritic cells (DCs), with the aim of improving antigen presentation and activation of antigen-specific immune responses [15][16][17][18][19][20][21]. We have reported that the delivery of HIV antigens through these receptors, even in minute amounts, induces strong and sustained T-and B-cell responses in vitro and in vivo in animal models, including non-human primates (NHPs) and humanized mice reconstituted with human hematopoietic stem cells (hu-mice) [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%